Performance of hot mix asphalt using peat modified asphalt binder - Bader Ali, Ahmed Suliman (2019)
In recent years, the road distresses have caused millions of ringgit to maintenance cost. Hence, allowed paving technologists to examine the benefits of introducing additives and modifiers. As a result modifiers such as fillers, extenders polymers (natural and synthetic), fibers among others, are introduced to be mixed with asphalt. This study was conducted to investigate the use of parit Nipah peat (PNpt) to be mixed with asphalt, both of unaged and aged conditions to improve the performance of asphalt mix. The physical properties, storage stability and rheological properties of base asphalt and PNpt modified asphalt (PNpt.M.A.) were measured. It was observed that the rheological properties differ considerably between the base asphalt and PNpt. The rheological changes associated with the ageing of PNpt.M.A are linked to a breakdown of the molecular structure of the binders to form a lower molecular weight peat substructure. Based on the SHRP rutting parameters, adding PNpt decreases rutting for the binder at high temperature rheological properties indicated that 5% PNpt or PNpt.M.A. 5 is the optimum content as a modifier with asphalt. After the optimum content of PNpt, tests were conducted to investigate the performance characteristics, where the mixes were prepared according to the wet process. Mechanical testing on the PNpt asphalt mixes have demonstrated that the asphalt mix stiffness, rutting performance at high temperature were found to be improved. Modification indices with the PNpt 5% showing a peak modification with 45.6% percentages increasing to enhancement towards against rutting deformations with consideration the effect of aging as an average of the mixture work interim of rutting resistance. However, the durability studies have indicated that PNpt are slightly susceptible with the presence of rutting. The stiffness modules of mixes were found to be affected by the testing temperatures and frequencies. As conclusion, asphalt pavement performance can be enhanced by using PNpt as modifier is major road distresses. In addition, it has the excellent potential for great modification of the asphalt binder and mixture.